A new wriggler of Eleotrid (Teleostei: Xenisthmidae) from Taiwan - Chen, I-Shiung; Harefa, Tonisman; Jiang, Guo-Chen; Chang, Chih-Wei (Zootaxa, 2022)
A new wriggler of genus Xenisthmus was collected from Taitung and Pingtung Counties, Taiwan, while using SCUBA diving of coral reef fish survey. The new species, Xenisthmus nigrolateralis, can be well distinguished from other congeners by the following unique combination of features: (1) fins: second dorsal fin rays I/13; anal fin rays I/13; pectoral fin rays16; (2) squamation: longitudinal scale series 68-70; perdorsal scales 23; (3) vertebral count 10+16=26; (4) preopercular canal present with rather more, 5 pores γ1, γ, δ, ε, and ε1 and (5) specific colouration: lateral side with broad, deep brown stripe from rear of lateral gill opening to caudal fin base, and caudal fin with median blackish brown mark, and upper and lower regions translucent, the base with a vertical black bar. The comparison of other congeners would be also discussed in this paper.